Capacity Increase Investigation of Cu2Se Electrode by Using Electrochemical Impedance Spectroscopy - Li, Xiuwan; Zhang, Zhixin; Liu, Chaoqun; Lin, Zhiyang (Frontiers in Chemistry, 2018)
Cu2Se nanoflake arrays supported by Cu foams are synthesized by a facile hydrothermal method in this study. The Cu2Se materials are directly used as an anode for lithium ion batteries, which show superior cycle performance with significant capacity increase. Combining with previous reports and scanning electron microscope images after cycling, the capacity increase caused by the reversible growth of a polymeric film is discussed. Electrochemical impedance spectroscopy is used to test the reversible growth of the polymeric film. By analyzing the three-dimensional Nyquist plots at different potentials during the discharge/charge process, detailed electrochemical reaction information can be obtained, which can further verify the reversible formation of a polymeric film at low potential.